L'umanesimo di Aristotele fra politica, conoscenza e educazione - Marco Salis (Firenze University Press, 2015)
According to the author of this study, the nature of Aristotle's work is, at the same time, humanistic and anthropocentric, unlike Plato's work, which is hu- manistic and theocentric. The author arrives at this conclusion through exami- nation of the philosopher's pedagogical ideas: the definition of the purposes and means of education is related to the quality of the responses on the organisation of human societies, on the problem of the common good, and on the nature of man both as a rational being and with reference to his place in the natural world.